2003
DOI: 10.1093/qjmed/hcg152
|View full text |Cite
|
Sign up to set email alerts
|

Clinical predictors of acute coronary syndromes in patients with undifferentiated chest pain

Abstract: In addition to previously recognized predictors of ACS, it appears that indigestion or burning type pain predicts ACS in patients attending the emergency department with acute, undifferentiated chest pain. Diagnosis of acute 'gastro-oesophageal' chest pain should be avoided in this setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
1
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 11 publications
5
35
1
2
Order By: Relevance
“…Most often the patient will note chest or upper body discomfort and dyspnea as the predominant presenting symptoms accompanied by diaphoresis, nausea, vomiting, and dizziness. [17][18][19] Isolated diaphoresis, nausea, vomiting, or dizziness are unusual predominant presenting symptoms. 20 Atypical or unusual symptoms are more common in women, the elderly, and diabetic patients.…”
Section: Prehospital Management Patient and Healthcare Provider Recogmentioning
confidence: 99%
See 1 more Smart Citation
“…Most often the patient will note chest or upper body discomfort and dyspnea as the predominant presenting symptoms accompanied by diaphoresis, nausea, vomiting, and dizziness. [17][18][19] Isolated diaphoresis, nausea, vomiting, or dizziness are unusual predominant presenting symptoms. 20 Atypical or unusual symptoms are more common in women, the elderly, and diabetic patients.…”
Section: Prehospital Management Patient and Healthcare Provider Recogmentioning
confidence: 99%
“…Although the presence of clinical signs and symptoms may increase suspicion of ACS, evidence does not support the use of any single sign or combination of clinical signs and symptoms alone to confirm the diagnosis. [17][18][19]112 When the patient presents with symptoms and signs of potential ACS, the clinician uses ECG findings (Figure 1, Box 4) to classify the patient into 1 of 3 groups: The interpretation of the 12-lead ECG is a key step in this process, allowing not only for this classification but also the selection of the most appropriate diagnostic and management strategies. Not all providers are skilled in the interpretation of the ECG; as a consequence, the use of computer-aided ECG interpretation has been studied.…”
Section: Ed Evaluation and Risk Stratification (Figure 1 Boxes 3 Andmentioning
confidence: 99%
“…Numerous studies do not support the use of any clinical signs and symptoms independent of electrocardiograph (ECG) tracings, cardiac biomarkers, or other diagnostic tests to rule in or rule out ACS in prehospital or emergency department (ED) settings. [215][216][217][218][219][220][221][222][223][224][225][226][227][228] To improve ACS outcome, all dispatchers and EMS providers must be trained to recognize ACS symptoms, even if atypical. It is reasonable for dispatchers to advise patients with potential cardiac symptoms to chew an aspirin (160 to 325 mg), providing the patient has no history of aspirin allergy and no signs of active or recent gastrointestinal bleeding (Class IIa, LOE C).…”
Section: Special Resuscitation Situations Acute Coronary Syndromesmentioning
confidence: 99%
“…[20][21][22] Using combinations of history and physical examination findings to discriminate patients with serious causes of chest pain is often not possible. 23 In our study, we demonstrated wide variation in the decision to hospitalize Medicare beneficiaries with chest pain, nearly twofold in the lowest and highest quintile of hospitals and that patients treated in hos- pitals with higher admission rates for chest pain are less likely to have AMI within 30 days of their index events and less likely to die.…”
Section: Discussionmentioning
confidence: 99%